Evaluation of Compliance with IMO FAL Regulations in International Shipping Standards: A Comparative Study between Indonesia and Singapore - Marisya Agustirani; Surya Desta; Azrul Asyikin (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2025)
This study examines and compares the compliance levels of Indonesia and Singapore with the International Maritime Organization’s Convention on Facilitation of International Maritime Traffic (FAL Convention), focusing on its implications for international shipping standards. The background of this research lies in the growing importance of administrative efficiency and digital integration in port operations as essential determinants of maritime competitiveness. Both countries, situated along vital international trade routes, have ratified the FAL Convention; however, their implementation outcomes differ significantly. The main objective of this study is to evaluate how far both states have operationalized facilitation obligations, including the use of standardized FAL forms, electronic reporting systems, Maritime Single Window (MSW) implementation, and the enforcement of inspection facilitation principles. Using a qualitative comparative method based on document analysis, the research reviews legal frameworks, official port authority guidelines, and international compliance reports. The findings reveal that Singapore exhibits full compliance across all FAL indicators, supported by an integrated MSW, mandatory electronic data exchange, and consistent application of inspection facilitation procedures. Indonesia demonstrates partial compliance, with major ports showing progress in digital reporting but with smaller ports still constrained by limited interoperability, uneven enforcement, and fragmented administrative coordination. These variations stem from institutional capacity gaps, regulatory misalignment, and differing levels of digital readiness. The study concludes that enhancing inter-agency coordination, standardizing inspection procedures, and improving MSW interoperability are critical strategies for Indonesia to strengthen its compliance with the FAL Convention and improve port facilitation performance within global maritime governance.